Households' responses on medical pluralism: Dynamics and determinants of access to traditional medicines in India - Pratap C. Mohanty; Kamal Sharma (Elsevier, 2021)
The Indian healthcare practice is pluralistic and unique since it is poised with many challenges. High out of pocket (OOPE) expenditure, scanty institutional facilities, and expensive private healthcare, etc. have strong bearing on adoption of traditional health care practices besides socio-cultural and other gradients. The paper addresses the dynamics and determinants of the access to traditional medicines in India using the representative dataset of the national sample survey (71st and 75th round) conducted in 2014 and 2017-2018. The analysis includes descriptive statistics, conditional Logit regression with marginal effects and Tobit regressions models. Results confirm increased access to traditional medicines even in case of major ailments which has reduced the OOPE on healthcare. The Covid19 pandemic has synergised the use of AYUSH owing to its immunity-boosting measures. The paper also incorporates some of the recent policy initiatives taken over recently in India to facilitate the Ayurveda, Yoga and Naturopathy, Unani, Sowa Rigpa, Siddha and Homoeopathy (AYUSH).